Miliary Tuberculosis Initially Presenting as an Isolated Hepatic Abscess - Chang Won Ha; Sang Deok Shin; Myung Ji Goh; Byeong Geun Song; Wonseok Kang; Dong Hyun Sinn; Geum-Youn Gwak; Yong-Han Paik; Moon Seok Choi; Joon Hyeok Lee (The Korean Journal of Gastroenterology)
Hepatic tuberculosis, typically associated with miliary tuberculosis, can occasionally present as localized liver lesions. This case report describes a 77-year-old male presenting with persistent abdominal pain and fever, following an endoscopic retrograde cholangiopancreatography for bile duct sludge removal. Subsequent computed tomography revealed focal liver lesions. Despite initial treatment with antibiotics for a suspected inflammatory liver abscess, his condition did not improve. A liver biopsy was performed, revealing caseous granulomas, and the tuberculosis polymerase chain reaction result was positive. The patient was diagnosed with primary hepatic tuberculosis, which later disseminated. Oral anti-tuberculosis therapy was initiated and is currently being closely monitored. This case emphasizes the importance of considering hepatic tuberculosis in the differential diagnosis of liver lesions, particularly in cases involving cholestatic liver function tests, and persistent symptoms unresponsive to conventional antibiotics.